Laser Surface Modification of Powder Metallurgy-Processed Ti-Graphite Composite Which Can Enhance Cells' Osteo-Differentiation - Šugár, Peter; Ludrovcová, Barbora; Kalbáčová, Marie Hubálek; Šugárová, Jana; Sahul, Martin; Kováčik, Jaroslav (Materials (Basel, Switzerland), 2021)
The paper examines the surface functionalization of a new type of Ti-graphite composite, a dental biomaterial prepared by vacuum low-temperature extrusion of hydrogenated-dehydrogenated titanium powder mixed with graphite flakes. Two experimental surfaces were prepared by laser micromachining applying different levels of incident energy of the fiber nanosecond laser working at 1064 nm wavelength. The surface integrity of the machined surfaces was evaluated, including surface roughness parameters measurement by contact profilometry and confocal laser scanning microscopy. The chemical and phase composition were comprehensively evaluated by scanning electron microscopy, energy-dispersive X-ray spectroscopy and X-ray diffraction analyses. Finally, the in vitro tests using human mesenchymal stem cells were conducted to compare the influence of the laser processing parameters used on the cell's cultivation and osteo-differentiation. The bioactivity results confirmed that the surface profile with positive kurtosis, platykurtic distribution curve and higher value of peaks spacing exhibited better bioactivity compared to the surface profile with negative kurtosis coefficient, leptokurtic distribution curve and lower peaks spacing.
Keywords: osteo-differentiation; laser micromachining; stem cell; graphite–titanium composite; biocompatibility; surface morphology